CP-005 Assessment of drug-drug interactions involving psychiatric agents in hospitalised patients. (24th March 2015) - Freire, M; Sobrino, C; De Sebastián, M; Balade, L; Bravo, M; Lara, C; Villamañán, E; Herrero, A
Abstract : Background: The use of psychiatric agents in hospitals increases the complexity of pharmacotherapy and the risk of drug–drug interactions. Purpose: To assess the frequency and clinical relevance of interactions associated with the use of antipsychotics, anxiolytics, antidepressants and sedative/hypnotics in a hospital. Material and methods: Cross-sectional observational study in which the treatment of adult patients admitted to a general hospital (1, 350 beds) was reviewed. The investigators, using a computerised physician order entry program, evaluated pharmacotherapy of inpatients involving antipsychotics, anxiolytics, antidepressants and sedatives/hypnotics. They assessed drug-drug interactions and their clinical significance as described in the literature. Reference sources were the Micromedex database and the Spanish Society of Hospital Pharmacist's professional guide to drug interactions. Results: Treatment of 393 patients was analysed. Of these, 179 (45.5%) were prescribed one of the drugs studied; 53.6% were female and 46.4% male with mean age 65 (SD ± 17.7) years. The average number of drugs prescribed per patient was 12 (SD ± 4.41). A total of 221 drug interactions was detected (9.5% pharmacokinetic, 90.5% pharmacodynamic), affecting 70.4% of patients. A total of 42.8% were due to prescription of antipsychotics, 31.1% due to antidepressants, 18.5% to anxiolytics and 7.6% to hypnotics/sedatives. The medical specialties involved were surgery (22.4%), oncology (11.1%), cardiology (8.9%), internal medicine (8.9%) and psychiatry (8.4%). Based on clinical significance, 47.5% of interactions were severe, 25.3% moderate and 27.1% mild. Potential interactions with significant clinical effects were haloperidol-tramadol (increased seizure risk), escitalopram-low molecular weight heparin (increased risk of bleeding) and midazolam-morphine (increased sedation). Three contraindicated combinations were detected: escitalopram-metoclopramide for increased QT interval, linezolid-amitriptyline for serotonin syndrome and risperidone-metoclopramide for neuroleptic syndrome and extrapyramidal reactions. Conclusion: Prescription of antipsychotic drugs, antidepressants, anxiolytics and sedatives/hypnotics to inpatients is very common. These drugs cause numerous drug interactions, which can potentially have serious consequences for hospitalised patients. References and/or acknowledgements: Psychiatric Department No conflict of interest.